App Inventor2 Learning Basketball at Grade X Senior High School - Indrianto, Dani; Setyawati, Heny; Kusuma, Donny Wira Yudha (Universitas Negeri Semarang, 2017)
The purpose of this study is to involve the growing sophistication of technology on education and determine the feasibility and the improvement of learning outcomes using a smartphone. This study uses a development which is the basis for developing models produced. The results of the small scale trials, improving every aspect obtained is the cognitive aspects of 59%, 49% psychomotor, and affective 0%. Gain test results criterion level of cognitive, psychomotor and the average yield was high (value ≥ 0.7). On the affective aspect, low level criteria (value ≤ 0.3). From large-scale trial found an average increase in each school obtained on the cognitive aspects of between 49% -54%, psychomotor aspects 48% -55%, affective 0%. Data validation field tests of media experts 83.33%, experts PE 85%, experts basketball 97.5% and an average of four teachers at 93.1%, as well as the responses of students amounted to 91.68%. Gain test results criterion level of cognitive, psychomotor and the average yield was high (value ≥ 0.7). On the affective aspect, low level criteria (value ≤ 0.3). Based on the above results, it can be concluded that the instructional media PE (basketball) Android-based high school students eligible for use in learning.